A "think piece" on intelligence, investigation and prosecution. Issue 3 (3rd July 2017) - Fitzpatrick, David
Abstract : Purpose: The purpose of this paper is to expose the failure of the criminal justice system of England and Wales to provide an effective response to widespread fraud and to point to sources from which a new doctrine may be created. The author's approach draws on public sources, in particular, recent Home Office publications, the work of the House of Commons Home Affairs Committee and studies undertaken by the Mayor of London's offices in 2014/2015. Design/methodology/approach: The paper uses a critical assessment of the criminal justice system based on the author's own experience as a fraud prosecutor. Findings: Among the findings is that, while the failings of the current system have been apparent for some years, the extent and depth of the same failings have not been publicly realised, nor sufficiently acknowledged by the authorities. It has become obvious that the traditional response of the criminal justice system, when employed against fraud, will fail for want of anything corresponding to the resources required. A new doctrine will emerge as the Proceeds of Crime Act 2002 is revised and more flexibly employed. The Criminal Finances Bill also holds much promise, in particular, with its new offences akin to money laundering and the provision of powers of investigation at a significantly lower level of command among investigators. However, there remains an apparent reluctance in law enforcement to explain its methodology or to support reform, which would allow a fuller sharing of intelligence and appreciations of threats posed by fraud derived from intelligence with the financial services sector and the victim public. Originality/value: The value of the paper is derived from the author's long experience as a fraud prosecutor and as an adviser to the government, on fraud and organised crime, in a closely related jurisdiction with similar problems, but where greater success has been achieved, namely, Hong Kong.